INTERNET OF THINGS (IoT) PADA PROTOTIPE PENDETEKSI KEBOCORAN GAS BERBASIS MQ-2 dan SIM800L - Sri Mluyati; Sumardi Sadi (Jurnal Teknik, 2018)
The use of the Internet of Things is currently becoming popular, using communicating objects. Likewise in the context of gas . To find out gas leakage and early detection of gas leakage, a prototype gas leak detector was made using MQ-2 and SIM800L. This gas detector uses Arduino nano, gas sensors (MQ-2), RFID, 16x2 and i2c LCDs, Buzzers, and SIM800L modules. as a wireless connection using SMS. The method used in this study is the experimental method. This tool is implemented and processed on hardware and provides the right and expected results. Gas Leaks will be detected on gas levels starting at 52%.